LITERASI KEUANGAN BAGI PENGURUS KOPERASI AMBOY BANTUL - Fitriyani, Lita Yulita (Dharma: Jurnal Pengabdian Masyarakat, 2021)
This activity was conducted at amboy bantul cooperative consisting of producers and sellers of various processed foods, especially foods made from bananas. The type of business conducted by this cooperative is a business to save loans. This cooperative is a MicroFinance Institution (LKM)Based on the observations, some of amboy bantul cooperative managers are not yet understanding financial literacy. Literacy is an individual's ability and skills in reading, writing, calculating, solving problems, processing data, conveying information and understanding information related to daily life. Initially, the board of AMBOY Bantul Cooperative did not yet understand the meaning of depreciation or depreciation of fixed assets that should be presented in the financial statements.Therefore, this activity is intended to improve the ability of AMBOY  Bantul cooperative management in understanding how to prepare the correct financial statements, especially in recognizing the burden of depreciation and accumulated depreciation of fixed assets by providing counseling and training. After the management of this cooperative participated in counseling and training, finally AMBOY Bantul cooperative managers can understand how to calculate the burden of depreciation, accumulated depreciation and presentation in financial statement.They understand that depreciation expense accounts (all cooperative fixed assets) are presented on the Remaining Business Results Report as a reduction in service income accounts. They also understand that accumulated depreciation accounts reduce the acquisition price of each fixed asset presented on the balance sheet. Some administrators of AMBOY Bantul Cooperative can finally compile cooperative financial statements in accordance with Financial Accounting Standards for Entities Without Public Accountability (ETAP)